Yellowmargined Leaf Beetle: A Pest of Cole Crops - Elena M. Rhodes; Oscar E. Liburd (EDIS)
The yellowmargined leaf beetle is a pest of cole or cruciferous crops that is native to South America. Since first reported in Mobile, Alabama, in 1947, the beetle has spread throughout the Gulf Coast from Texas to Florida and up into Georgia and North Carolina. It has also been reported from Illinois and California. Not considered a major pest in conventionally grown cruciferous crops because it is susceptible to a wide range of insecticides, it poses a significant threat to the growing organic industry in the southeastern United States. It is a particular problem on Asian greens such as mizuna, mibuna, and napa cabbage, as well as on other high-value cruciferous crops like turnip, mustard, and watercress. This 4-page fact sheet was written by Elena M. Rhodes and Oscar E. Liburd, and published by the UF Department of Entomology and Nematology, September 2014.